HUBUNGAN DUKUNGAN KELUARGA DENGAN TINGKAT STRES MAHASISWA S1 KEPERAWATAN DALAM MENYUSUN SKRIPSI DI UNIVERSITAS PAHLAWAN TUANKU TAMBUSAI TAHUN 2020 - ANISAH ULFAH; ALINI ALINI; PUTRI EKA SUDIARTI (Jurnal Ners, 2020)
Thesis is a final project that students must do to get a bachelor's degree. In the process, there are many students who experience difficulties so that it has an impact on psychology and physicality ranging from mild to severe such as anxiety, fear, confusion and stress. In dealing with stress, students need family support to be able to reduce the level of stress they experience. The purpose of this study was to analyze the relationship between family support and stress levels in undergraduate nursing students in semester VIII in compiling a thesis at Tuanku Tambusai University in 2020. The design of this study was descriptive correlational with a cross sectional study design with total sampling method. The population of this study was 62 students of S1 Nursing semester VIII with a total sample of 60 people. Data collection using a questionnaire sheet. The data analysis used was univariate and bivariate analysis with the Chi Square test. The results showed a relationship between family support and stress levels in students in compiling their thesis with a p-value of 0.006 (p